Clinical and radiological outcomes of magnetically controlled intramedullary lengthening nails in adolescents and young adults: a retrospective cohort study - Mehmet Ali Talmaç; Melih Civan; Ergün Mendes (Journal of Orthopaedic Surgery and Research)
Abstract Background Magnetically controlled intramedullary lengthening nails offer a fully internal approach to limb lengthening, avoiding complications associated with external fixators such as pin site infections and soft tissue transfixation. While their use in adults is well-documented, evidence regarding their safety and efficacy in adolescents and young adults remains limited. Methods This retrospective cohort study evaluated the clinical and radiological outcomes of 24 limb lengthening procedures performed in 18 adolescent and young adult patients between 2022 and 2024 using PRECICE® intramedullary lengthening nails. Patients aged ≤ 18 years with a minimum of 9 months follow-up were included. Lengthening parameters, regenerate morphology, complication rates, and inter-group comparisons were analyzed. Results A total of 24 long bone segments (femur, tibia, and humerus) underwent lengthening in 19 sessions. The mean follow-up period was 18.8 months. The average length gained was 45.7 ± 10.5 mm, with a distraction rate of 1.0 ± 0.1 mm/day. Complications requiring return to the operating room occurred in 16% of cases, while 5.3% had minor unresolved issues at treatment completion. Radiographic analysis revealed favorable regenerate morphology, and no case showed regenerate insufficiency. Statistical comparison revealed a significantly higher distraction rate in femoral versus tibial lengthenings (p = 0.036). Conclusions Fully internal limb lengthening using magnetically controlled nails is a safe and effective option for adolescents and young adults, with a low rate of complications and high-quality regenerate formation. These findings support broader adoption of internal lengthening in younger patients, particularly in centers with trained teams and appropriate patient selection.